2017
DOI: 10.20343/teachlearninqu.5.2.6
|View full text |Cite
|
Sign up to set email alerts
|

Changes in approaches to learning over three years of university undergraduate study

Abstract: This study aimed to evaluate and compare approaches to learning by a longitudinal cohort of undergraduate students as they progressed from their first to third years of study in anatomy and physiology. The Approaches and Study Skills Inventory for Students (ASSIST) was completed at the beginning and end of their first year of university study, and in their final semester. At first year, a surface learning approach predominated; however, at third year, students showed a significant increase in their use of deep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 48 publications
(61 reference statements)
1
11
1
2
Order By: Relevance
“…In our study, students involved in problem-based, hands-on laboratory stations experienced the most situational interest, situational intrinsic motivation, and behavioral engagement, followed by students engaged in problem-based case studies and lecturebased treatment groups. Our findings add to a growing body of literature documenting the benefits of problem-based and hands-on activities (Barrows, 1986;Dhanapal & Shan, 2014;McDonald, Reynolds, Bixley, & Spronken-Smith, 2017). Many have shown that students tend to prefer problem-based learning and hands-on activities to lecture-based instruction, finding these approaches more enjoyable, interesting, and motivating (Abrahams, 2009;Hodson, 1990;Middleton, 1995).…”
Section: Discussionsupporting
confidence: 62%
“…In our study, students involved in problem-based, hands-on laboratory stations experienced the most situational interest, situational intrinsic motivation, and behavioral engagement, followed by students engaged in problem-based case studies and lecturebased treatment groups. Our findings add to a growing body of literature documenting the benefits of problem-based and hands-on activities (Barrows, 1986;Dhanapal & Shan, 2014;McDonald, Reynolds, Bixley, & Spronken-Smith, 2017). Many have shown that students tend to prefer problem-based learning and hands-on activities to lecture-based instruction, finding these approaches more enjoyable, interesting, and motivating (Abrahams, 2009;Hodson, 1990;Middleton, 1995).…”
Section: Discussionsupporting
confidence: 62%
“…In the future, there appears to be particular need for longitudinal research that use the ASSIST to examine occupational therapy students’ study approach development over time. Such research is gaining momentum in related healthcare fields (Mcdonald et al ., ; Reid et al ., ). Future research might also assess study approaches and their development in relationship with the students’ personal characteristics (Bonsaksen, Sadeghi & Thørrisen, ; Prat‐Sala & Redford, ) as well as their perceptions of the learning environment (Fryer & Ginns, ; Kreber, ; Sun & Richardson, ), both of which promising lines of inquiry.…”
Section: Discussionmentioning
confidence: 99%
“…Many factors influence students’ academic results in higher education, and there is general agreement that students’ own engagement with the curriculum is important for their subsequent grades (Bonsaksen, Brown, Lim & Fong, ; Diseth, ; Kusurkar, Ten Cate, Vos, Westers & Croiset, ; Mcdonald, Reynolds, Bixley & Spronken‐Smith, ; Salamonson et al ., ; Valadas, Almeida & Araujo, ). Over the last decades, the “approaches to studying” concept has denoted students’ general orientation towards studying in academic settings (Richardson, ).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the articles published by TLI fit in this genre. Recent examples include an Australian analysis of students' perceptions of their learning outcomes, engagement, and satisfaction with a technology-facilitated flipped approach in a core course in entrepreneurship (Fisher, Ross, LaFerriere, & Maritz, 2017); a New Zealand study that evaluates and compares approaches to learning by a longitudinal cohort of undergraduate students as they progressed from their first to third years of study in science using the Approaches and Study Skills Inventory for Students (McDonald, Reynolds, Bixley, & Spronken-Smith (2017); and an analysis of the representations of higher education within 11 topgrossing critically acclaimed films released in 2014, co-authored by two students and a member of faculty in a Canadian university (Johnstone, Marquis, & Puri, 2018).…”
Section: Empirical Research Articles: Analyzing and Reporting Data Tomentioning
confidence: 99%